Blockchain Education Concept 4.0: Student-Centered iLearning Blockchain Framework - Prawiyogi, Anggy Giri; Aini, Qurotul; Santoso, Nuke Puji Lestari; Lutfiani, Ninda; Juniar, Hega Lutfilah Juniar (JTP - Jurnal Teknologi Pendidikan, 2021)
Technological developments encourage digitization in the learning process. Inversely proportional to the results of competency evaluation which are still centralized. Cause competitiveness and competence of students that are not measured quantitatively. The application of micro-teaching can be an option in solving existing problems. Combining gamification and blockchain makes the learning process more enjoyable with game techniques, where activities such as learning, lecture assignments, and assessments are documented transparently and have reliable security. This student-centered learning process is called GamiChain (Gamification Blockchain). This blockchain gamification-based learning application is also an important activity that can be a brilliant breakthrough in education. This application aims to encourage the student creativity ecosystem, to make students have a more competitive spirit to compete with maximum capabilities. And can display learning outcomes in the form of certificates that are accurate in authenticity and can be used in the industrial world. GamiChain can form an official standard of learning by documenting lectures permanently, transparently, and distributed formally and informally into the Blockchain network with the help of smart contracts. The Gamification method in education is used in this research. Results Evaluation of blockchain application in education through GamiChain (Gamification Blockchain) can benefit universities to create official certifications and increase confidence in student scores transparently and sustainably that they can control.